Public sources in the municipality of Poços de Caldas - MG: practices of consumption and their implications to user’s health - da Silva, Rômulo Magno; Botezelli, Luciana; Mello, Ivani Souza (Seven Editora, 2023)
The objective of this work was to evaluate the habits and practices of the inhabitants of Poços de Caldas - Minas Gerais, regarding the consumption of water resources from alternative sources (fontes/minas). The information was collected through questionnaires, sent by e-mail. The return rate of the questionnaires was 36.6%. 90.2% of respondents had already consumed water from alternative sources and 9.8% said they had never consumed it. It was found that the consumption was monthly: 54.5%; less than monthly: 24.5%; weekly: 9.1% and daily: 19.1%. 50.1% of the interviewed consumed the resource at the place of source and 49.9% consumed it at home. For 74.5% the consumption purpose was human and for 25.5%, consumption was for other purposes. 69.1% did not use any technique and 30.1% used simplified techniques. About the places of storage and transport, 7.3% used boxes; 50.1%, gallons, buckets, and clay buckets and 22%, reused packages. 20% did not consume water at home. In view of the results obtained, it was found that the practices and habits of the interviewers represented health risks, that suggests that policies for monitoring sources and disseminating information are recommendable. DOI: https://doi.org/10.56238/colleinternhealthscienv1-084